Future integrated mobility-energy systems: A modeling perspective. (March 2020) - Muratori, Matteo; Jadun, Paige; Bush, Brian; Bielen, David; Vimmerstedt, Laura; Gonder, Jeff; Gearhart, Chris; Arent, Doug
Abstract: After over a century of petroleum dominance, the transportation sector is on the verge of radical transformations driven by rapid technology advancement of alternative fuels, automation, information technologies that create new mobility options and business models, and policies at all levels of government. While the technologies and fuels that will move people and goods in the future remain uncertain, the future transportation system will be more integrated with smart buildings, the electric grid, renewables, and information ecosystems, allowing for great opportunities to exploit these interconnections. Modeling tools for analyzing integrated mobility-energy systems require a deep understanding of these interconnections, of the infrastructure required to support alternative fuel vehicles, and a more nuanced understanding of transportation energy needs across multiple segments and spatiotemporal scales. In this paper, we assess the landscape of existing tools used to represent and model future mobility systems and their interactions with other energy systems. We conclude that (a) out-of-sample extrapolation of emerging trends and future anticipated developments is more important than ever due to the plethora of factors driving disruptive change in mobility systems; (b) understanding adoption opportunities for alternative fuel light-duty vehicles requires modeling intra-household decisions affecting travel demand and mode choice; (c) mobility and energy systems need to be modeled as an integrated continuum, breaking the traditional approach in which dynamic energy supply models use relatively simple transportation demand and vice-versa; and (d) increased spatiotemporal fidelity and scalability are required to dynamically couple transportation/mobility and energy supply models and capitalize on these unprecedented interconnection opportunities. Highlights: Landscape of existing tools used to represent and model future mobility systems. Modeling future mobility-energy systems requires an integrated approach. Need for out-of-sample extrapolation of emerging and anticipated trends. Need to model intra-household decisions affecting travel demand and mode choice. Increased spatiotemporal fidelity and scalability to couple mobility-energy systems.